Instructional Methods Applied by Visually Impaired Teachers in Teaching Students with Intellectual Disability - Hakiman, Hakiman (TADRIS: Jurnal Pendidikan Islam, 2020)
AbstractThis study aims at investigating the instructional methods applied by the Islamic religious education teacher with visual impairment in teaching the students with mild and moderate intellectual disability.This study is a qualitative descriptive research. The data were collected through in-depthinterview, observation and documentation techniques. Triangulation is used as the technique to facilitate the validation of data, including the methods, sources and theories. Meanwhile, the data analysis technique includes data reduction, data display and conclusion drawing.The findings of this study reveal that in the learning activities, the visual impaired teacher uses several methods, including lecture method, discussion method, demonstration method, and assignment method on students with mild intellectual disability. Meanwhile, the methods used on students with moderate intellectual disability include lecture method, discussion method, storytelling method, demonstration method and drilling method. The process is equipped with learning media, including audio-visual media, screen reader technology, printouts in which self-helped students also provide assistance to the teacher.This study describes the learning process of Islamic religiouseducation conducted by visually impaired teacherand it is expected that the findings will provide insight and input for teachers in teaching students with intellectual disabilities both in schools for special needs and similar inclusive schools. Keywords: Methods, Visually Impaired Teachers, Intellectually Disability, Islamic Religious Education